2018
DOI: 10.1183/13993003.02189-2017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of pulmonary tuberculosis by combined molecular and immunological methods

Abstract: Diagnosing pulmonary tuberculosis (TB) may be delayed until culture results become available.We ascertained the accuracy of a stepwise diagnostic algorithm for the rapid diagnosis of pulmonary TB by GeneXpert from sputum and/or bronchoalveolar lavage (BAL) followed by a specific BAL ELISPOT assay in patients with a suspected diagnosis of pulmonary TB at a clinical referral centre in Germany.Among 166 patients with a presumptive diagnosis of pulmonary TB, 81 cases were confirmed by culture from sputum and/or BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Similarly, IGRAs showed a moderate performance in ruling out ATB in Xpertindividuals in a high-TB/HIV burden setting (Theron et al, 2012). Intriguingly, a recent study showed that T-SPOT with BALF with a cut-off of >4000 early secretory antigenic target-6-or culture filtrate protein-10-specific interferon-g-producing lymphocytes per 10 7 lymphocytes was able to identify 88.9% of AFB -/Xpert -patients with culture-proven MTB (Jafari et al, 2018), although the sample size of this study is small. It will be interesting to determine if BALF-based T-SPOT MDC and TBAg/PHA ratios can better predict TB disease within a large AFB -/Xpertpopulation.…”
Section: No Ntmmentioning
confidence: 99%
“…Similarly, IGRAs showed a moderate performance in ruling out ATB in Xpertindividuals in a high-TB/HIV burden setting (Theron et al, 2012). Intriguingly, a recent study showed that T-SPOT with BALF with a cut-off of >4000 early secretory antigenic target-6-or culture filtrate protein-10-specific interferon-g-producing lymphocytes per 10 7 lymphocytes was able to identify 88.9% of AFB -/Xpert -patients with culture-proven MTB (Jafari et al, 2018), although the sample size of this study is small. It will be interesting to determine if BALF-based T-SPOT MDC and TBAg/PHA ratios can better predict TB disease within a large AFB -/Xpertpopulation.…”
Section: No Ntmmentioning
confidence: 99%
“…Currently, the Xpert© MTB/RIF assay (Cepheid Inc, Sunnyvale, Calif., USA) is what comes close to a rapid molecular diagnostic tuberculosis test although it is dependent on good quality sputum sample ( 19 ). Tuberculosis diagnosis can also be through the detection of host biomarkers or pathogen biomarkers such as Mycobacterium tuberculosis (Mtb) products ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Individually, IgG and IgA antibodies against MIF could not achieve good sensitivity and specificity, respectively, in order to replace conventional diagnostics. In previous studies, higher predictive power could be achieved when tests of multiple markers were combined [25][26][27]. Because statistically significant differences in anti-MIF antibody levels existed between study groups, it may be possible to increase the predictive power of the existing method by combining it with other known markers.…”
Section: Discussionmentioning
confidence: 99%